Thai Tea Seed (Camellia oleifera) Oil Favorably Affects Plasma Lipid Responses in Hamsters Fed High‐Fat Diets. Issue 2 (21st December 2018) - Suealek, Nuchanart; Yokoyama, Wallace H.; Rojpibulstit, Panadda; Holt, Roberta R.; Hackman, Robert M.
Abstract : Coronary heart disease (CHD) is the leading cause of death worldwide. Dietary inclusion of monounsaturated fatty acids (MUFA) such as olive oil (OO) can reduce CHD risk. Tea seed oil (TSO) from Camellia oleifera grown in Thailand, with a MUFA content similar to OO, may be an alternative to OO when a higher cooking smoke point is desired. The lipid profiles, liver histology, and serum chemistries of hamsters fed high‐fat diets (TSO, OO, grape seed oil or butter; 14% by weight) are analyzed. After three weeks of feeding, TSO and OO groups have similar plasma low‐density lipoprotein cholesterol (LDL‐C), very‐low‐density lipoprotein cholesterol (VLDL‐C), triacylglycerols (TAG), high‐density lipoprotein cholesterol (HDL‐C), and total cholesterol (TC) levels. Moreover, TC/HDL‐C and LDL‐C/HDL‐ C ratios are also comparable. Similar to the OO group, the TSO group has significantly lower plasma LDL‐C, VLDL‐C, TAG, TC, and a lower TC/ HDL‐C ratio as compared to the butter group. Some minor liver pathological lesions commonly found in rodents fed high‐fat diets are observed. Thai TSO may be a healthy option for cooking, and clinical studies are warranted. Practical Applications : With its high smoking point, TSO is attractive to Asian consumers for their styles of cuisine. As it is produced locally, its price is cheaper than imported OO. This study demonstrates TSO's health benefits in lowering lipid profiles similar to OO. Based on this fact, this study supports Thai TSO cultivation in northern Thailand as a means of increasing rural villagers' income. Hamsters are divided into five groups: tea seed oil, olive oil, grape seed oil, low fat, and butter. Tea seed oil favorably lowers plasma low‐density lipoprotein cholesterol (LDL‐C) in hamsters fed high‐fat diets. Abstract : Hamsters are divided into five groups: tea seed oil, olive oil, grape seed oil, low fat, and butter. Tea seed oil favorably lowers plasma low‐density lipoprotein cholesterol (LDL‐C) in hamsters fed high‐fat diets.